Analisis Kebutuhan E-Modul Interaktif Berbantuan Canva dan Flip Heyzine pada Materi Ekosistem di Kelas X SMA Negeri 5 Medan : (Analysis of the Needs of Interactive E-Modules Assisted by Canva and Flip Heyzine on Ecosystem Material in Class X of SMA Negeri 5 Medan) - Salsabilah , Shanata; Pulungan , Ahmad Shafwan S. (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to develop a Biology E-Module assisted by the Flip Heyzine application on the ecosystem topic that can be used in both school and out-of-school learning, as well as to determine its feasibility, user responses, and effectiveness in improving students’ learning outcomes. This research employed a Research and Development (R&D) approach using the 4D model (define, design, develop, and disseminate) by Thiagarajan. The research subjects consisted of two experts (material and media), one biology teacher, and 36 tenth-grade students from SMA Negeri 5 Medan. The instruments used included expert validation questionnaires, teacher response questionnaires, and student learning outcome tests.The results showed that the material expert validation score was 93.01%, media expert 96.25%, and teacher response 93.51%, all categorized as highly feasible. The effectiveness test produced an N-Gain value of 0.72, indicating that the e-module was effective in improving students’ learning outcomes. Therefore, the Flip Heyzine-assisted Biology E-Module on the ecosystem topic is declared valid, feasible, and effective as an innovative learning resource for biology instruction. Abstrak: Penelitian ini bertujuan menghasilkan E-Modul Biologi berbantuan aplikasi Flip Heyzine pada materi ekosistem yang dapat digunakan dalam pembelajaran di sekolah maupun di luar sekolah, serta mengetahui kelayakan, respon pengguna, dan keefektifannya terhadap hasil belajar siswa. Jenis penelitian ini adalah Research and Development (R&D) dengan model 4D (define, design, develop, dan disseminate) dari Thiagarajan. Subjek penelitian meliputi dua ahli (materi dan media), satu guru biologi, dan 36 siswa kelas X SMA Negeri 5 Medan. Instrumen yang digunakan berupa angket validasi ahli, angket respon guru, serta tes hasil belajar. Hasil penelitian menunjukkan bahwa validasi ahli materi mencapai 93,01%, ahli media 96,25%, dan guru 93,51%, ketiganya termasuk kategori sangat layak. Uji efektivitas melalui nilai N-Gain sebesar 0,72 menunjukkan bahwa e-modul efektif meningkatkan hasil belajar siswa. Dengan demikian, E-Modul Biologi berbantuan Flip Heyzine dinyatakan valid, layak, dan efektif sebagai bahan ajar inovatif pada materi ekosistem.